2003
DOI: 10.1002/art.11349
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis of the shoulder joint: Comparison of conventional radiography, ultrasound, and dynamic contrast‐enhanced magnetic resonance imaging

Abstract: Objective. To determine the role of ultrasound and magnetic resonance imaging (MRI) compared with conventional radiography in the detection of chronic and acute inflammatory manifestations of rheumatoid arthritis (RA) of the shoulder joint.Methods. Forty-three consecutive patients with known RA prospectively underwent clinical examination, radiography, ultrasound, and MRI of the shoulder joints. Each patient was assigned a clinical/laboratory score consisting of 7 parameters, including measurements of shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 106 publications
(57 citation statements)
references
References 35 publications
3
48
0
6
Order By: Relevance
“…US was more accurate than clinical examination in the detection of synovitis, which is consistent with the results of a number of earlier studies (3,7,24,30,41). However, we found more second and third MCP joints to be affected clinically than was evident by US.…”
Section: Us Scoring Of Finger Joint Synovitis In Rasupporting
confidence: 90%
See 1 more Smart Citation
“…US was more accurate than clinical examination in the detection of synovitis, which is consistent with the results of a number of earlier studies (3,7,24,30,41). However, we found more second and third MCP joints to be affected clinically than was evident by US.…”
Section: Us Scoring Of Finger Joint Synovitis In Rasupporting
confidence: 90%
“…A number of comparative imaging studies that have included US have been performed (3,(5)(6)(7)(22)(23)(24)(25). However, US scoring methods with quantitative assessment of joint inflammation have yet not been standardized or appropriately validated (26,27).…”
mentioning
confidence: 99%
“…The selected papers were then divided among the group members and assessed according to an agreed scoring sheet (for results of Evaluation score, see Table 1) 4,5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]…”
Section: Resultsmentioning
confidence: 99%
“…However, daily experience demonstrates that large joints are frequently involved in rheumatic diseases, and that involvement of large joints has an enormous impact on the patient's disability and prognosis (20). Hermann et al reported on shoulder involvement in up to 70% of patients with RA confirmed by MRI scanning (21). In addition, erosions of the elbow joint have been observed in 61% of patients with RA followed up for 15 years (22), whereas hip erosions were detected in 20% of patients with RA, and erosive changes of the knees were detected in 27% of patients with RA within a period of 12 years (7).…”
Section: Discussionmentioning
confidence: 99%